2022
DOI: 10.1002/ijc.33971
|View full text |Cite
|
Sign up to set email alerts
|

On the development of a neoantigen vaccine for the prevention of Lynch Syndrome

Abstract: Lynch Syndrome (LS) is an autosomal dominant genetic condition that causes a high risk of colorectal cancer. The hallmark of LS is genetic instability as a result of mismatch repair (MMR) deficiency, particularly in repetitive low complexity regions called microsatellites (MS). MLH1−/− mice deficient in MMR are prone to developing tumors in the colon, upon oral administration of dextran sodium sulfate (DSS), at a rate of more than 70%. Using this LS mouse model, we found a novel tumor neo‐antigen from a deleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In addition, several clinical and pre-clinical trials for LS and dMMR cancer are underway to test the safety and immunogenicity of frameshift peptide (FSP) neoantigen-based vaccine [ 94 , 95 , 96 ]. In a phase I/Iia clinical trial, 22 patients with advanced dMMR CRC received FSP neoantigen-based vaccine, and the results showed that vaccine-induced humoral and cellular immune responses were observed in all patients and no vaccination-induced severe adverse events occurred [ 95 ].…”
Section: Precision Medicine In Hereditary Crc Syndromesmentioning
confidence: 99%
“…In addition, several clinical and pre-clinical trials for LS and dMMR cancer are underway to test the safety and immunogenicity of frameshift peptide (FSP) neoantigen-based vaccine [ 94 , 95 , 96 ]. In a phase I/Iia clinical trial, 22 patients with advanced dMMR CRC received FSP neoantigen-based vaccine, and the results showed that vaccine-induced humoral and cellular immune responses were observed in all patients and no vaccination-induced severe adverse events occurred [ 95 ].…”
Section: Precision Medicine In Hereditary Crc Syndromesmentioning
confidence: 99%